Graduate Students Views in Using Search Engines for Thesis Writing - Casumpang, Stacy; Pedroso, John Erwin; Matullano, Isaiah Kurt; Tocong, Rochele Mae; Degomon, John Christian; Villanueva, Angel Marie (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
Search engine market found that Google held a prominent position as the preferred search engine among graduate students. As these students heavily depend on search engines to meet their academic requirements, enjoying advantages such as convenient search outcomes and increased confidence in utilizing web search engines for their thesis writing. This qualitative-descriptive research describes the behavioral intentions of graduate students in using search engines in their thesis writing. The study utilized semi-structured written interview to gather data through google forms and delivered using messenger application to the informants who were purposively selected using purposeful sampling. The information gathered was then analyzed through thematic Analysis. The findings revealed that there are three (3) themes that emerge from the results, namely: Behaviors, Factors, Outcomes, and five (5) meaningful categories, namely: Stress free, Open Mindedness, Transitioning, Peer Influence, and Performance output. The study shows that their use of current technology helped graduate school students by maximizing the use of search engines in their skills in thesis writing.